Identification of a Novel Metabolic Target for Bioactive Triterpenoids Biosynthesis in Ganoderma lucidum - Xu, Juan; Wang, Yiyi; Zhang, Yi; Xiong, Kehui; Yan, Xiaoyun; Ruan, Shiyu; Wu, Xueqian (Frontiers in Microbiology, 2022)
Triterpenoids are crucial active ingredients of Ganoderma Lucidum (G. Lucidum) with various health benefits. Yet the low biosynthesis greatly restricts their industrial applications, novel metabolic engineering strategies are needed to further enhance Ganoderma triterpenoids production. Transcription factors play vital roles in the metabolic regulation of terpenoids, which are still scarce to study in G. Lucidum. Herein, a transcription factor GlbHLH5 (GenBank No. MZ436906.1) potential for metabolic regulation of Ganoderma triterpenes was identified for the first time. MeJA could increase Ganoderma triterpenoids biosynthesis, and GlbHLH5 significantly responded to MeJA induction, suggesting GlbHLH5 is a new target for Ganoderma triterpenoids overproduction. The regulatory effect of the newly identified target was further validated by homologous gene overexpression and silence in G. lucidum. It’s demonstrated that overexpression of GlbHLH5 significantly increased triterpenoids accumulation and the key enzyme genes transcription in the biosynthetic pathway, while silencing it displayed the opposite effect, indicating GlbHLH5 could positively regulate the triterpenoids biosynthesis by activating the synergistic expression of key enzyme genes in the biosynthetic pathway. Consequently, GlbHLH5 was identified as a positive regulator and novel metabolic engineering target for Ganoderma triterpenoids biosynthesis, it sheds new lights on the regulatory effect regulation and synthetic biology of Ganoderma triterpenoids.